Legal Development of Coastal Marine Management Based on the Idea of Pancasila - Jantje Tjiptabudy (Hasanuddin Law Review, 2018)
In relation to the positive law, the management of marine and coastal natural resources, there is also the rule of customary law. Customary law that still lives and develops in indigenous peoples also regulates the management system and utilization of natural resources in coastal and marine areas. Recognition of the rights of indigenous peoples is constitutionally contained in the 1945 Constitution of the State of the Republic of Indonesia where the state recognizes the existence of the Customary Law Community. In Maluku, marine potency management in general is still done traditionally known as marine customary rights that have been going on for generations but not yet fully recognized either by the government or entrepreneurs who are actually important partners in the development process.